2021
DOI: 10.1186/s12916-021-02179-y
|View full text |Cite
|
Sign up to set email alerts
|

Within- and across-day patterns of interplay between depressive symptoms and related psychopathological processes: a dynamic network approach during the COVID-19 pandemic

Abstract: Background In order to understand the intricate patterns of interplay connected to the formation and maintenance of depressive symptomatology, repeated measures investigations focusing on within-person relationships between psychopathological mechanisms and depressive components are required. Methods This large-scale preregistered intensive longitudinal study conducted 68,240 observations of 1706 individuals in the general adult population across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…Longer periods of strictly implemented SDPs were tied to longer periods of deleterious depressive symptom expression after the SDPs were lightened. This finding is in line with the etiological explanations of depressive problems, describing how prolonged constellation of symptoms for longer periods carry over across time through increased connectivity between symptoms (e.g., American Psychiatric Association, 2013; Ebrahimi, Burger, et al, 2021). The findings point toward additive risk of long-term exposure to such socially isolating and mobility restricting protocols.…”
Section: Discussionsupporting
confidence: 84%
“…Longer periods of strictly implemented SDPs were tied to longer periods of deleterious depressive symptom expression after the SDPs were lightened. This finding is in line with the etiological explanations of depressive problems, describing how prolonged constellation of symptoms for longer periods carry over across time through increased connectivity between symptoms (e.g., American Psychiatric Association, 2013; Ebrahimi, Burger, et al, 2021). The findings point toward additive risk of long-term exposure to such socially isolating and mobility restricting protocols.…”
Section: Discussionsupporting
confidence: 84%
“…One previous temporal dynamic network study (26) suggested that connectedness and inperson social contact were key resources for lower depressive symptomatology, and that loneliness was a key factor in predicting depression. Our data replicates the strong contemporaneous and between-person relationship between loneliness and depressive symptoms, and we also found a (small) contemporaneous relationship between momentary adherence to social distancing behaviours and loneliness -but not depressive symptoms.…”
Section: Mental Health and Adherence Behaviourmentioning
confidence: 96%
“…Only few studies have employed temporal dynamic network analysis in the context of mental health during the COVID-19 pandemic. For example, Ebrahimi et al (26) show that experiences of helplessness during the pandemic increase depressive symptoms and identified particular risk factors for carry-over effects. Haucke et al (27) compared networks between lockdown and non-lockdown periods in Germany and found increases in loneliness during lockdown periods, which in turn predicted worse mental health.…”
Section: Introductionmentioning
confidence: 99%
“…This quantifies the magnitude of a specific node's direct connections to all other nodes, to yield the overall importance of each node in the network. Strength centrality was visualised using radar plots, as previously recommended in the literature (Ebrahimi et al, 2021).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Symptoms of anxiety and depression have high prevalence in the general population and represent a considerable burden to societies worldwide (GBD 2019 Diseases andInjuries Collaborators, 2020). The prolonged constellation and long-term stability of such symptoms may emerge into mental health disorders (e.g., Ebrahimi et al, 2021), and while efficacious treatments are available, many individuals do not respond to current treatments (Barth et al, 2016;Cipriani et al, 2009). In response, there have been calls highlighting the importance of efforts to prevent depression and anxiety in the population (Bienvenu & Ginsburg, 2007;Cuijpers et al, 2012).…”
Section: Introductionmentioning
confidence: 99%